ANALISIS PENGENDALIAN PIUTANG PT. KLM - Yuyun Istifadah; Anita Handayani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research is to identify and evaluate the accounts receivable control system adopted by PT KLM. This research is conducted using qualitative methodology. There are both primary and secondary data used. Using interview and observation tactics to obtain data from store managers, cashiers, and billing parties for the purpose of publishing articles. This investigation was done at the PT KLM office in Lamongan, East Java. On the basis of the findings, the authors conclude that the implementation of internal control at PT KLM is less successful at regulating its receivables, as indicated by inadequate control, supervision, monitoring, and risk assessment. Several internal and external forces have contributed to this. However, PT. KLM's knowledge, communication, and control environments are adequate.